Reconstructing Child Protection for Victims of Crime: Integrating Family Law, Institutional Practice, and Maqāṣid al-Sharīʿah (A Study of UPTD PPA Aceh) - Tifany Mahdina Putri; Fakhrurrazi M. Yunus; Gamal Akhyar; Idrus Afandi Akbar (Tabayyanu : Journal Of Islamic Law, 2025)
Child protection for victims of criminal acts remains a pressing global concern, particularly in jurisdictions where legal frameworks coexist with complex socio-cultural structures. While existing scholarship has largely focused on normative legal analysis or institutional responses, insufficient attention has been given to the interplay between family dysfunction and institutional intervention in shaping the effectiveness of child protection systems. This article addresses this gap by examining the implementation of child protection mechanisms at the Regional Technical Implementation Unit for Women and Children Protection (UPTD PPA Aceh) through an integrative analytical framework combining family law, victim-centered justice, and maqāṣid al-sharīʿah. Employing a socio-legal approach with qualitative methods, this study integrates doctrinal legal analysis with empirical data derived from in-depth interviews, field observations, and case documentation. The findings demonstrate that UPTD PPA Aceh has developed an integrated protection model encompassing legal assistance, psychological recovery, and social reintegration. However, the effectiveness of this model is significantly constrained by structural limitations, weak family support systems, and persistent socio-cultural stigma. This article contributes to the literature by advancing a conceptual framework that situates child protection at the intersection of family responsibility and institutional governance. It further argues that sustainable protection mechanisms require a systemic integration of legal norms, institutional capacity, and family-based resilience, which is normatively consistent with the objectives of maqāṣid al-sharīʿah, particularly the preservation of life (ḥifẓ al-nafs) and lineage (ḥifẓ al-nasl).